2015
DOI: 10.5812/archneurosci.22804
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Blood Loss and Hospital Stay in Patients With Major Lumbosacral Surgeries: A Multi-Center, Prospective, Cross-Sectional Survey

Abstract: Background: Blood loss during spinal decompression and fusion is high and at times more than the patient's total estimated blood. Increased blood loss may increase the risks of morbidity and eventually length of hospital stay (LOS). Objectives: The aim of this study was to identify predictor factors of blood transfusion requirements and the length of hospital stay in adult patients who underwent lumbosacral surgery. Materials and Methods:This was a multicenter cross-sectional study to predict factors of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…The present study identified PRC preparation factors that predicted the risk of PRC transfusions in developing countries. The prevalence of PRC transfusion (43%) during the study period at this spine referral center hospital was similar to some studies (40%-81%) 2,13,15 but in contrast with other previous studies (5%-32%) 9,12,14 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The present study identified PRC preparation factors that predicted the risk of PRC transfusions in developing countries. The prevalence of PRC transfusion (43%) during the study period at this spine referral center hospital was similar to some studies (40%-81%) 2,13,15 but in contrast with other previous studies (5%-32%) 9,12,14 .…”
Section: Discussionsupporting
confidence: 88%
“…Potential clinical predictors include baseline characteristics, such as female sex [8][9][10] , age 8,9 , and BMI 1 ; comorbidities, such as type II diabetes mellitus 8,11 , hypertension 11 , pulmonary disease 3,8,9 , anticoagulant or antiplatelet 8 , ASA classification 1,9,12 ; preoperative laboratory parameters, such as preoperative Hct 8,9 and platelets 14 ; operative data, such as operative time 8,9,[11][12][13] , decompression level and fusion method 1,8,9,[11][12][13] , sacral fusion 12 , number of pedicular screw fixations 3 , use of tranexamic acid 20 , and estimated blood loss (EBL) 14 .…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…(87) Ένας ακόµη περιορισµός είναι ότι η µετεγχειρητική αιµοσφαιρίνη εκτιµήθηκε άµεσα µετά την επέµβαση. Ο Grant et αl (162) (16)(17)(18)(19)(20) Πιο συγκεκριµένα, ο Miri et al (165) σε µια µελέτη του 2015 καταλήγει στο συµπέρασµα πως σηµαντικότερος παράγοντας πρόβλεψης των διεγχειρητικών απωλειών αίµατος είναι ο αριθµός επιπέδων σπονδυλοδεσίας. Ο Li et al (163) καταλήγει επίσης στο συµπέρασµα πως τα επίπεδα σπονδυλοδεσίας καθορίζουν σε µεγάλο βαθµό τις ανάγκες µετάγγισης.…”
Section: μεταγγιση αιματος (αυτόλογη αλλογενής)unclassified